Therapeutic delivery with V‐amylose. Issue 6 (15th February 2021) - Prasher, Parteek; Fatima, Rabab; Sharma, Mousmee
Abstract: The helical structure of V‐amylose offering a superior encapsulation affinity compared with the other polysaccharides, especially toward the amphiphilic or hydrophobic molecules; in addition to providing a higher resistance toward enzymatic hydrolysis support its applications as a potential drug delivery vehicle. Mainly, the glycosidic linkages and –CH2 – groups forming the hydrophobic cavity of V‐amylose helix, and the glycosyl hydroxyl groups constituting its hydrophilic periphery promote the loading of a diverse range of molecules via van der Waals forces and hydrogen bonding interactions. These properties enable a high‐loading efficiency, targeted delivery, and controlled release of the cargo drug molecules by V‐amylose. Besides, V‐amylose presents characteristics of an ideal drug delivery system, such as biocompatibility, physiological benevolence, nonimmunogenicity, and biodegradability. The V‐amylose polysaccharide chains fold into left‐handed single helix comprising of six glucose units in each turn having a pitch height of 7.91–8.17 Å. These structural features of V‐amylose differentiate it from the parent amylose polysaccharide and enable the accommodation and nanoencapsulation of a wide range of therapeutics in the former. The tightly packed helical structure of V‐amylose provides extraordinary resistance toward digestion by amylase compared with the linear polysaccharides, which supports the application of V‐amylose as controlled drug release systems. The activity of the amylase enzyme produced by salivary glands, pancreas, gastrointestinal tract, and gut microbiota on amylose‐based drug delivery vehicles promote enzyme‐sensitive controlled oral and colon‐specific release of the encapsulated drug. The single helical V‐amylose with hydrophobic core and hydrophilic periphery forms inclusion complexes that improve the absorption and permeation of drugs having a high clogP index. The present commentary highlights the distinguished features of V‐amylose as an imminent drug delivery system.